Mindcare: an elderly centered mental health care mobile application - Zannat, Nahreen; Nowshin, Nadia; Mahmud, Murni (MNNF Publisher, 2021)
ICT (Information and communication technology) has blessed us with smart devices and technologies that are now playing a vital role in our existence. Majority of the mobile applications have extensive features and functionalities in the efforts to make our lives better and easier, however, elderly people in the other hand struggle to use these technologies for the exact same reason. The struggles were amplified during the Coronavirus (COVID-19) pandemic, whereby the maintenance of lockdown and Standard Operating Procedure (SOP) pushed almost everything to be transferred into the digital platform. Additionally, increased digital barriers and prolonged period of isolation, along with the fear towards the pandemic itself, there was a substantial increase in the number of people suffering from mental health disorders worldwide. While there are increasing mental health apps available to help the global population with this issue, most of them were designed and developed for the young or adolescents. Meanwhile, elderly people were left behind to find a platform online for counselling or treating their mental health due to increasing digital barrier. In this paper, the authors highlighted challenges and digital gaps between elderly people before proposing a solution with minimalistic design with the elderly perspective in mind to minimize their struggles and maintain their mental health well-being.